2014
DOI: 10.1002/anie.201408374
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Water Splitting at Thin Film Tungsten Trioxide Photoanodes Bearing Plasmonic Gold–Polyoxometalate Particles

Abstract: Tungsten trioxide (WO3) is one of a few stable semiconductor materials liable to produce solar fuel by photoelectrochemical water splitting. To enhance its visible light conversion efficiency, we incorporated plasmonic gold nanoparticles (Au NPs) derivatized with polyoxometalate (H3PMo12O40) species into WO3. The combined plasmonic and catalytic effect of Au NPs anchored to the WO3 surface resulted in a large increase of water photooxidation currents. Shielding the Au NPs with polyoxometalates appears to be an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
32
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(32 citation statements)
references
References 35 publications
0
32
0
Order By: Relevance
“…It was suggested that the catalytic effect of Au-PMo 12 O 40 3-and the plasmonic effect of the AuNPs both contributed to the improved PEC performance. They further suggested that Au-PMo 12 O 40 3-supports the separation of charge carriers 144. …”
mentioning
confidence: 97%
“…It was suggested that the catalytic effect of Au-PMo 12 O 40 3-and the plasmonic effect of the AuNPs both contributed to the improved PEC performance. They further suggested that Au-PMo 12 O 40 3-supports the separation of charge carriers 144. …”
mentioning
confidence: 97%
“…The enhancement of the electromagnetic field does not exclusively depend on the interparticle distance of two plasmonic particles but on a number of different factors such as the particle size and shape, the surrounding Reprinted with permission from [8]. Copyright 2011, Nature Publishing Group dielectric environment [75,147], and the incident wavelength [28]. Certainly, the strong dependence of the LEMF on these factors can be used to design photocatalysts with enhanced activity.…”
Section: Local Electromagnetic Field Enhancementmentioning
confidence: 99%
“…Certainly, the strong dependence of the LEMF on these factors can be used to design photocatalysts with enhanced activity. Recently, Pu et al developed a catalytic system for photoelectrochemical water oxidation [28]. Their photocatalyst was designed from two different gold nanoparticles, spheres and rods, which absorb light and thus enhance the local electromagnetic field in their vicinity at different wavelengths ( Fig.…”
Section: Local Electromagnetic Field Enhancementmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6][7] An aspect of the research in materials science has reported about the electrochemical performances about these compounds. [1][2][3][4][5][6][7] An aspect of the research in materials science has reported about the electrochemical performances about these compounds.…”
mentioning
confidence: 99%